Multi-dimensional void fraction measurement of transient boiling two-phase flow in a heated rod bundle - Takahiro ARAI (The Japan Society of Mechanical Engineers, 2015)
A subchannel void sensor (SCVS) was developed to measure the cross-sectional distribution of void fraction in a 5×5 heated rod bundle with o.d. 10 mm and heated length 2000 mm, and applied to a boiling two-phase flow experiment under the atmospheric pressure condition assuming at an accident or in a spent fuel pool in a boiling water reactor (BWR). The SCVS comprises 6-wire by 6-wire and 5-rod by 5-rod electrodes. The wire electrodes of 0.2 mm in diameter are arranged in lattice patterns between the rod bundle, while the electric conductance value in a region near one wire and another corresponds to local void fraction in the central-subchannel region. The local void fractions at 32 points (= 6×6-4) can be obtained as a cross-sectional distribution. The local void fractions near the rod surface at 100 points (= 4×25) can be also estimated by the conductance value in a region between one wire and one rod. The devised sensors are installed at five height levels along the axis to acquire two-phase flow behavior. A pair of SCVS is mounted at each level and placed 30 mm apart to estimate the one-dimensional phasic velocity distribution based on the cross-correlation analysis of both layers. The temporal resolution of void fraction measurement is 1600 frames (cross-sections) per second. The axial and radial power profile of the heated rod bundle are uniform, and eight pairs of sheath thermocouples are embedded on the heated rod to monitor its surface temperature distribution. The boiling two-phase flow experiment, which simulated a boil-off process, was conducted with the devised SCVS and experimental data was acquired under various inlet flow velocity, rod bundle power and inlet subcooling conditions. The experimental results were presented by the axial and cross-sectional distributions of void fraction, phasic velocity and bubble-chord length.